COMPARING THE VALUE OF TRANSRECTAL ULTRASOUND AND MAGNETIC RESONANCE IMAGING IN THE DIAGNOSIS OF PROSTATE CANCER (Vietnam Journal of Community Medicine, 2026)
Objective: This study aimed to assess the diagnostic value of transrectal ultrasound and magnetic resonance imaging within a unified sample.Subjects and methods: A cross-sectional study was conducted from January 2020 to April 2023 at Hoa Hao Medical Center, Ho Chi Minh city. A total of 201 medical records of patients aged over 50 years were retrospectively reviewed to collect transrectal ultrasound, magnetic resonance imaging, and biopsy-confirmed diagnoses of prostate cancer.Results: On transrectal ultrasound, heterogeneous echogenicity, abnormal nodules, and abnormalities of the prostatic capsule achieved diagnostic accuracies ranging from 78.1-79.6%. On magnetic resonance imaging, the presence of suspicious lesions or a Pi-rads score greater than 3 yielded accuracies of 68.2% and 65.2%, respectively, while a Pi-rads score greater than 4 or detection of regional lymph nodes showed accuracies of 70.2% and 63.2%, respectively.Conclusion: Preliminary findings suggest that transrectal ultrasound higher diagnostic accuracy than magnetic resonance imaging. Future studies should place greater emphasis on the concurrent comparison of transrectal ultrasound and magnetic resonance imaging to further strengthen the evidence regarding their diagnostic value in prostate cancer.
Keywords: Transrectal ultrasound, magnetic resonance imaging, prostate cancer.